1D morphodynamical modelling of macro-tidal sandy beaches under pure tidal currents - Huynh, Van Long (2019)
This research aims to study bed level evolution of a sandy beach under tidal effects over a long-time scale, using a fully-coupled hydro-morphodynamical numerical model.